Income Growth and its Distribution from Eisenhower to Obama: The Growing Importance of In-Kind Transfers (1959-2016) - James Elwell; Kevin Corinth; Richard V. Burkhauser (Institute of Labor Economics (IZA), 2019)
We provide the first survey-based look at levels and trends in income and its distribution from 1959 to 2016 by linking Current Population Survey data from 1967 through 2016 with decennial Census data for 1959. We find that the dramatic decline in the market income of the middle class (measured as the median American tax unit or the mean value of the middle quintile of American tax units) began in 1969. However, we find that this decline was more than offset by government tax and transfer programs – especially in-kind transfers. Conventional measures of median income and income inequality that exclude the market value of in-kind transfers will substantially understate the impact of government policies in offsetting the stagnation of median market income growth and the rise in market income inequality since 1969.
Keywords: D31; C81; 330; long-term growth trends (1959-2016); median income; income inequality; survey-based CPS data; market income; valuing in-kind transfers; full-income series